Analysis of the Korean generic medicine market: Factors affecting the market share of generic medicines - Dong‐Sook Kim; Jihye Shin; Jusun Chung (Wiley, 2022)
Abstract This study probed the market share of generic medicines by patients' age and sex, type of medical facilities, route of administration, number of generic brands, market size (drug expenditure), and therapeutic class and investigated factors associated with a high market share of generic medicines in Korea. We analyzed using national health insurance data between 2010 and 2019. The dependent variable was the generic medicine market share, measured as the number of prescriptions and expenditures. Multivariable regression analysis was conducted using the numbers of generic brands, market size by each ingredient and therapeutic class, relative price, the number of prescriptions, and therapeutic class. Total pharmaceutical expenditures have increased due to the high use of single‐source drugs. The number of prescriptions and expenditures for generic medicines were 0.3 billion prescriptions and $7.8 billion, respectively, accounting for 46.5% and 46% of the total market. Multivariate analysis showed that the number of prescriptions (>20 thousand) and the market size of main active ingredients (>$1 million) were associated with an increased market share, whereas the number of generic brands (compared to <3) was associated with reduced generic medicine market share. In conclusion, we found that supply policies to promote the market entry of generic medicines by mandating price consistency between generic medicines and off‐patent original medicines had limitations in increasing the generic medicine market share. Policy should be put in place both to ensure the timely market entry of generic medicines and to promote the use of cheaper generic medicines.